Nonlinear relationships and volatility spillovers among house prices, interest rates and stock market prices - Liu, Hsiang-Hsi; Chen, Sheng-Hung (International Journal of Strategic Property Management, 2016)
This paper addresses the interaction between interest rates and the significant increases in both Taiwanese house and stock market prices seen in recent years. Changes in house prices impact banks’ nonperforming loans, whereas changes in interest rates directly influence the ability of individuals and businesses to pay loan interest, accentuating the co-movements between house and stock mar-ket prices. We investigate the nonlinear relations and volatility spillovers among house prices, interest rates and stock market prices using monthly data from January 1985 to March 2009 for Taiwan. We find that the Smooth Transition Vector Error Correction GARCH (STVEC-GARCH) model has the best forecasting ability based on goodness of fit tests while showing a nonlinear and co-integrated relation among the three variables. Specifically, house price leads stock market returns when the interest rate is led by either house price or stock market returns. The volatility of stock market returns has significant impacts on interest rates, implying that borrowers should be aware of stock market fluctuations and thus strengthen their risk management because of unexpected changes. First Publish Online: 14 Dec 2016